Lean Transformation Practices in Healthcare - Efe, Omer Faruk; Nal, Mustafa (IGI Global, 2025)
This study investigates the benefits of adopting lean management in the healthcare sector, focusing on its impact on hospital management, employees, and patients. By advocating for the widespread implementation of lean management practices, this research aims to contribute to the healthcare management literature, emphasizing its role in enhancing communication and operational efficiency. The study was conducted in a public hospital in Turkey, with data collected between July 16, 2022, and January 31, 2023. A Value Stream Mapping (VSM) approach was employed to analyze the existing workflow and develop a "current state" map. Subsequently, lean transformation principles were applied to design a "future state" map, providing insights into potential process improvements. The findings culminate in a set of recommendations aimed at optimizing operational efficiency and strengthening communication within healthcare settings. © 2026, IGI Global Scientific Publishing. All rights reserved.
Keywords: Health care; Hospitals; Human resource management; Lean production; Communication efficiency; Health-care managements; Healthcare sectors; Hospital management; Lean management; Lean transformation; Management practises; Operational efficiencies; Value stream mapping; Work-flows; Efficiency